High energy emission in blazars - Celotti, A (2002)
Different scenarios which have been proposed for the production of high energy radiation in blazars will be briefly summarized. Recent results on the energy spectral distribution of high redshift radio-loud quasars are then considered in the context of the blazar phenomenology and their consequences for our understanding of jets are discussed. Finally, a possible scenario for the origin of X-ray emission from large scale jets, as detected by Chandra, is presented.